The extra virgin olive oil handbook - Peri, C. (Claudio) (Chichester, West Sussex, UK : John Wiley & Sons, 2014)
According to European legislation, extra virgin is the top grade of olive oils. It has a superior level of health properties and flavour compared to virgin and refined olive oils. Mediterranean countries still produce more than 85% of olive oil globally, but the constant increase of demand for extra virgin olive oil has led to new cultivation and production in other areas of the world, including California, Australia, China, South Africa and South America. At the same time, olive oil's sensory properties and health benefits are increasingly attracting the attention and interest of nutrition.
10.4 Control pointsChapter 11 Olive milling and pitting; 11.1 Introduction; 11.2 Milling machines; 11.3 Pitting machines; References; Chapter 12 Olive paste malaxation; 12.1 Basic phenomena in malaxation; 12.2 Malaxers; References; Chapter 13 Centrifugal separation; 13.1 Introduction; 13.2 The three-phase process; 13.3 The two-phase process; 13.4 Decanters; 13.5 Disc centrifuges; 13.6 Final comments and remarks; Further reading; Chapter 14 Filtration of extra-virgin olive oil; 14.1 Introduction; 14.2 Filtration principles; 14.3 The filter media; 14.4 Filtration equipment.
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher.
Keywords: Olive oil -- Handbooks, manuals, etc; TECHNOLOGY & ENGINEERING -- Food Science; Olive oil; Olive oil -- Handbooks, manuals, etc; Olive oil; Electronic books; Handbooks and manuals; Electronic books